Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations GENERAL INTRODUCTION 13 advancing, as the pupil develops, from appeals based on feelings to those based on reason. Young children form habits through love, fear, and imitation, but these habits have a better chance of being retained through life if they can withstand the moral and intellectual criticism which will be brought to bear upon them at later stages of the individual development. The infant will act in various ways because his teacher approves, or because his teacher acts in these ways; but he will only continue to perform such actions in later life when he understands why his teacher approved them or performed them, and is satisfied by such reasons. It is clear, then, that an education in cleanliness involves far more than the mere lessons, though these are essential to it. There must be a background, an atmosphere. The school itself, as a social community, must express in all ways a disapproval of uncleanliness of all kinds. Cleanliness is approved, and uncleanliness disapproved. This involves not merely the personal example of teachers, but also a fixed, invariable attitude on their part. It involves that the child who is not clean, who makes no effort to be clean, has to be made to feel that unless he conforms in this respect he stands outside the school. The extent to which this can be carried out, consistently with the development of other ideals — such as justice and charity — depends so much upon the environment from which children are drawn and their home circumstances, that little that is definite can be said regarding it. The methods by which it may be achieved, again, depend so much upon the school staff, that it is here also impossible to make precise recommendations. But it is clearly in general inadvisable to make the child who falls short of the school's standard of personal cleanliness an object of scorn or of harsh treatment in the first instance, since we thus run the risk of making him hate strongly what we wish him to respect. A number of methods of encouraging the formation of 177/5/8/3